2012
DOI: 10.3109/09513590.2011.650744
|View full text |Cite
|
Sign up to set email alerts
|

CAG repeat polymorphism of androgen receptor gene and X-chromosome inactivation in daughters of women with polycystic ovary syndrome (PCOS): relationship with endocrine and metabolic parameters

Abstract: AR CAG repeat polymorphism appears to be unrelated with serum androgen levels. However, the short mwCAGn variant may have a possible impact on the lipid profile in PCOSd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…This study also confirm the elevation in particle number of LDL and a critical reduction in LDL size and assume that androgens may play an important role in pathogenesis of dyslipidemia in women with PCOS [21]. The exact mechanism of dyslipidemia and subsequent hyperandrogenism in PCOS is not clear; hyperandrogenism may lead to changes in lipoprotein levels either by affecting directly at the liver, or by changing body composition by favoring central adiposity [22]. Serum levels of triglycerides, LDL and VLDL is significant high in obese PCOS women comparing to weight matched controls.…”
Section: Discussionsupporting
confidence: 79%
“…This study also confirm the elevation in particle number of LDL and a critical reduction in LDL size and assume that androgens may play an important role in pathogenesis of dyslipidemia in women with PCOS [21]. The exact mechanism of dyslipidemia and subsequent hyperandrogenism in PCOS is not clear; hyperandrogenism may lead to changes in lipoprotein levels either by affecting directly at the liver, or by changing body composition by favoring central adiposity [22]. Serum levels of triglycerides, LDL and VLDL is significant high in obese PCOS women comparing to weight matched controls.…”
Section: Discussionsupporting
confidence: 79%
“…In addition to the aforementioned factors, familial and/or genetic predisposition may be involved in the increased cardiovascular risk in PCOS patients. The influence of genetic polymorphisms on the metabolic profile of PCOS patients has been studied, and positive associations have been found with lipid profiles ( 16 ), insulin and homocysteine levels ( 17 , 18 ), high body weight and abdominal adiposity ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the CAG repeat numbers differed between lean and obese women with PCOS, wherein the shorter CAG repeats showed up with a greater frequency in the obese-hyperandrogenic sub-type of PCOS women (120). The CAG repeat length and XCI patterns were later also investigated between the daughters of control women and women with PCOS in a Chilean cohort, but the study showed no difference between the two groups (143).…”
Section: Theories On Fetal Reprogramming and Developmental Origins Ofmentioning
confidence: 99%